A study examining the effects of changed rules of wrestling competitions on the muscular damage levels of the elite wrestlers - C. Berkan Alpay; Hasan Eker; Ozkan Isık; Serkan Hazar (Türk Spor ve Egzersiz Dergisi)
This study aims to examine the effects of changing rules of wrestling competitions on the elite wrestlers' muscular damage levels. Twenty male wrestlers from the wrestling team established by the Izmir Metropolitan Municipality, which competes in the 1st Wrestling League, volunteered to take part in the research. The age average of the wrestlers was 20.4±2.8 years, their average age of sports 7.45±4.29 years, their height average 173,8 ±4,97 cm, and weight average 77.4 ±16.22 kg. Some blood samples of 5 cc each were taken from each wrestler's forearm vein by means of the vacutainer (a closed blood taking system) for the two competitions separately before and after the competitions; and on 24th, 48th, and 72nd hours following the competitions in the research. For looking at the levels of Creatine Kinase (CK), Lactate Dehydrogenase (LDH), Aspartate Aminotransferase (AST), and Alanine Aminotransferase (ALT), serums were obtained by centrifuging the blood samples those taken to determine the levels of the skeletal muscle damages of the wrestlers at 1000 RPM for 20 minutes. The enzyme levels of the blood samples (the serum of which was decomposed) were determined by the SIEMENS ADVIA biochemistry auto-analyzer using the SIEMENS kit. While the repetitive measurements were assessed via one-way analysis of variance (ANOVA), the Bonferroni testing was applied in order to determine from which measurement times the differences were originated. The Paired Samples-ttesting, meanwhile, was performed in order to compare the blood samples collected from the athletes at same times for the both completed competitions having different rules. No significant difference was observed between AST and ALT values on the aminotransferase of the wrestlers according to two different rules (pËƒ0.05). Whereas significant differences were confirmed between the values of 48 hours after and 72 hours after the competition for the LDH values (p lt;0.05), no significant difference, on the other hand, were detected between other values (pËƒ0.05). Although significant differences were observed between the results obtained following competition and 72 hours after the competition for the CK values (p lt;0.05), there was no significant difference between other values (pËƒ0.05). Consequently, it was observed that when the wrestlers took part in two-day wrestling competitions, the basal values were reached 72nd hour after the competition, and no muscle damage remained, whereas when they took part in half-day wrestling competitions it was confirmed at the end of the 72nd hour that the LDH and CK levels of the wrestlers couldn't come close to the basal and the muscle damage was present (p lt;0.05).